The recent sediment of the Bay of Koper (Northern Adriatic) - Ogorelec, Bojan; Mišič, Miha; Faganeli, Jadran; Stegnar, Peter; Vrišer, Borut; Vukovič, Aleksander (Geologija, 1987)
The Bay of Koper is a marine basin up to 20 m deep with restricted sea water circulation. Sedimentologically, it is classified as silty clay, rich in foraminiferal and molluscan skeletons. The grain-size and the carbonate content of the sediment, ranging between 20 and 40%, increase towards the Bay entrance. At the Rižana river mouth the sedimentation conditions change from fluviatile to brackish and marine. The Corg. content in the surficial sediment varies between 0.4 and 2.7 % with the highest values found in the central part of the Bay. The content of the heavy metals Cd, Cr, Cu, Hg, Ni, Pb, Sb and Zn in surficial sediment is at the same level as found in the geochemical background of the borehole V-6 in the Sečovlje salt marsh. The present paper also presents the results of Chemical analyses of pore water and an outline of benthic communities.